Kolaborasi Stakeholder pada Pelaksanaan Inovasi Penanggulangan Bencana Gempa Bumi di Nusa Tenggara Barat Tahun 2018 - Suryanuddin; Annisah (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
Innovations made by the government in dealing with the 2018 West Nusa Tenggara earthquake disaster (NTB) face several challenges. Construction of the house is targeted to be completed within a year, but the two-year run is still not completed. There are double data, not absorbed funds, until the number of houses built has not been in accordance with target becomes a serious problem. In fact, the stakeholders involved are very much. At the beginning of the quarter of 2021 reported the construction of earthquake resistant houses (RTG) in all NTB areas above 97%. Therefore, it is interesting to be further reviewed how the success of disaster management breakthroughs in NTB can achieve the targets and roles of various stakeholders. This study was conducted based on the study of documents from central and local government documents as well as literature reviews from journal articles during April 2021. The results of the study showed that the intensive collaboration and synergy from various stakeholders, played a big role in addressing the problems. Data validation conducted by BRI plays a big role in overcoming double data. RTG design from the Kementerian PUPR makes it easy for people to plan and rebuild their homes. TNI is present to assist technically in accelerating development. Facilitators assist the community in planning, applying for funds, implementation, and reporting. These efforts make the problems faced when the implementation of innovations in disaster management are resolved. These efforts, making breakthroughs in disaster management can be carried out. Each stakeholder has an equally important role in synergizing and collaborating with all stakeholders to support the achievement of disaster management objectives.